Penatalaksanaan Senam Kaki Diabetik Terhadap Kadar Gula Pada Asuhan Keperawatan Pasien Diabetes Melitus - Tuti Elyta; Sari Octarina Piko (Yayasan Literasi Sains Indonesia, 2022)
Diabetic foot exercise is one of the independent measures that must be taken to prevent the risk of gangrene in patients with diabetes mellitus.The purpose of this study is to gainreal experience and knowledge and be able to document the management of diabetes exercise on blood sugar levels in Diabetes Mellitus nursing care. This research method is a type of scientific paper that uses a descriptive method with a case study approach to explore the problem of Nursing Care in two patients with Diabetes Mellitus. Nursing care was carried out on two patients which was carried out on 24-26 August 2020. The target sample is elderly adult patients. The results of the study of sugar levels before the diabetic foot exercise was carried out on Ny. A is 238 mg/dl while Mr. D is 135 mg/dl. sugar levels after diabetic foot exercise on Ny. A is 190 mg/dl at a TnD of 130 mg/dl. The comparison of sugar levels on the third day on Mrs. A was 48 mg/dl on Tn D of 5 mg/dl. Based on the conclusion, progress notes for the two patients who underwent diabetes exercise management on sugar levels in the nursing care of Diabetes Mellitus patients, the comparison of the results of the analysis found that Mrs A and Mr D had a good decrease in the value of their blood sugar levels.